Leveraging Non-formal Action Research to Enhance Teacher Research Activity at a Pedagogical University in Republic of Kazakhstan - Berikkhanov, Aiman; Wilson, Elaine; Sarsenbayeva, Lyaziza; Sapargaliyeva, Bayan; Assilbayeva, Fatima; Iskakova, Aigul (Jurnal Arbitrer, 2024)
The study was conducted with the aim of identifying the possibilities for implementing the informal research method of Action Research into the educational process of a pedagogical university as a tool for enhancing the research activity of university teachers in Kazakhstan. The significance of mastering this method by pedagogical university faculty is grounded in their ability to disseminate their experience, involving students—future teachers—in a cyclical process of continuous research and transformation of their pedagogical practices. As a result of the literature review, the advantages of Action Research were highlighted, particularly in terms of activating personal, professional, and environmental resources that were previously underutilized in traditional formal research formats. The relevance of the study lies in the necessity to examine global experiences with informal research methods, focusing on the feasibility of their implementation with consideration of the specific context of Kazakhstan. The article describes the process of conceptualizing the informal method of Action Research, diagnosing awareness and demand for this method among young pedagogical university faculty, developing and testing a program for its implementation, evaluating its effectiveness, ensuring post-course support, and determining the prospects for integrating the method on a national scale. Methods such as surveys, pilot studies, formative experiments, and Action Research tools were applied. A pilot implementation of Action Research was conducted to develop the research activity of young faculty members at Abai University, considering their needs within the framework of a modular professional development program titled “Action Research – the Foundation for Developing a Pedagogue-Researcher Model.” Analysis of the results confirmed the effectiveness of implementing the method in enhancing the research activity of teachers and transforming them into researcher-teachers. Based on the review and feedback analysis, the prospects for the expanded integration of informal research methods into the practice of education in Kazakhstan were identified.